Study on nanodot OSLD in air cavity using 12 MeV electron beam radiotherapy - Othman, Farahamizah (Universiti Sains Malaysia, 2024)
Electron beam radiotherapy is valued for its ability to precisely target cancerous tissues while minimizing damage to healthy ones, but it faces challenges when air cavity disrupts the intended dose distribution. Accurate dosimetry is crucial to ensure the prescribed dose reaches the target while sparing healthy tissues. This research focuses on analyzing Percentage Depth Dose (PDD) curves using Optically Stimulated Luminescent Dosimeters (OSLD) and comparing them with Ionization Chamber measurements under varying air cavity thicknesses (4 cm, 6 cm, and 8 cm). The study utilized a linear accelerator at 12 MeV, employing solid water phantoms to simulate tissue and expanded polystyrene for air cavities. Measurements were taken at different depths to evaluate how air cavities affect dose distribution. The results revealed discrepancies between OSLD and Ionization Chamber measurements, with OSLD generally overestimating the dose, especially in the buildup region. In this study, both Optically Stimulated Luminescent Dosimeters (OSLD) and Ionization Chambers demonstrated closer agreement in dose measurements below the air cavity, with discrepancies of 31.7, 12.9, and 3.1 observed across all cavity thicknesses. However, both methods struggled to accurately estimate doses at the centre and surface of the air cavity.